SOME BIOLOGICAL ASPECTS OF SCALLOPED HAMMERHEAD SHARKS (Sphyrna lewini Griffith & Smith, 1834) CAUGHT FROM COASTAL FISHERIES IN THE EASTERN INDIAN OCEAN - Umi Chodrijah; Bram Setyadji (Research Center for Fisheries, 2015)
Indonesia has the largest chondrichthyan fishery in the world, with a reported of 105,000 and 118,000 tonnes landed in 2002 and 2003 respectively. Scalloped hammerhead shark was either targeted or by-catch from this fishery, mostly for its fins. Despite of the growing concern around the world, the availability of biological data of this species, especially in the Eastern Indian Ocean is still lacking. The objectives of this paper are to present some biological information (size composition and sex ratio) of the scalloped hammerhead, from coastal fisheries in Eastern Indian Ocean. The data used for the analysis comprised of two components, i.e. survey data in 2010 (February, March, June, August, October and December) and data from daily monitoring shark landing in 2013 (January to December). Substantially lower mean size, more immature sharks and more frequent of female caught over years showed that scalloped hammerhead shark in the Eastern Indian Ocean are facing intensive fishing pressure which could lead to overfishing. This could harm the sustainability of scalloped hammerhead shark resource in the long run. The relationship between clasper length and total length was positively correlated where every 5 cmTL increment on clasper length adding 51 cmTL on total length.